Situation Report: Poland, 16 November 1960 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Parliamentary Debates Academic Freedom: Travel Abroad Agricultural Circles Trade Union Elections New Rate of Exchange of the Rouble [Ruble] Motor Transport Alcoholism Pouched